2004
DOI: 10.1103/physrevlett.93.017401
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Symmetry Breaking under Core Excitation in Graphite: Polarization Correlation in Soft X-Ray Recombination Emission

Abstract: A recombination emission spectrum is applied to study the local lattice distortion due to core excitation in graphite. The recombination emission spectrum reveals a long low-energy tail when the C 1s electron is excited to the σ * core exciton state. This indicates a large local lattice distortion around the excited carbon atom within a core hole lifetime (∼10fs). Theoretical calculation based upon an ionic cluster model well reproduces the experiments. The strong polarization correlation between incident and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 24 publications
7
39
1
Order By: Relevance
“…Unlike photoelectron spectroscopies it is non-sensitive to sample charging, and is particularly useful for crystalline bulk insulator studies for materials, like BeO, which are not easily obtained as thin films without serious stoichiometry issues. A few recent RIXS studies [1,2] are closely related to this present work. Ma et al [1] observed the long energy loss tail to the elastic scattering peak, while in the absorption spectrum only a relatively sharp core exciton peak was observed.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Unlike photoelectron spectroscopies it is non-sensitive to sample charging, and is particularly useful for crystalline bulk insulator studies for materials, like BeO, which are not easily obtained as thin films without serious stoichiometry issues. A few recent RIXS studies [1,2] are closely related to this present work. Ma et al [1] observed the long energy loss tail to the elastic scattering peak, while in the absorption spectrum only a relatively sharp core exciton peak was observed.…”
Section: Introductionsupporting
confidence: 59%
“…[2,4]. When the excitation energy is increased even further and reaches values of approximately 130 eV, a satellite band, similar to the LET, appears again to the off-resonant X-ray emission spectra, although its intensity then is substantially weaker.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…A few RIXS studies [4,5] are closely related to the present work. Ma et al [4] observed the long energy loss tail to the elastic scattering peak, while in the absorption spectrum only a relatively sharp core exciton peak was observed.…”
Section: Introductionmentioning
confidence: 64%
“…Two kinds of selftrapped excitons (STE) have been identified-excitons with axial localization of the hole component (STE1) and excitons 5 Deceased.…”
Section: Introductionmentioning
confidence: 99%